Capacity and power analysis on inclined screw conveyor using DEM simulation - Ahmad Faishol; Mulyadi; Edi Widodo (University of Muhammadiyah Malang, 2023)
DEM is a method based on the theory of molecular dynamics that can simulate the movement of granular materials. One of the advantages of this method is it can simulate accurately without creating a real object. This study aims to determine how much influence the inclination of the screw conveyor has on the capacity and power of the motor. Corn shelled was used as a test with continuous filling of 1000 ft3/hour for 20 seconds, while modeling by screw conveyor 2 meter long at positions 00, 200 and 450 with variations in speed of 50 rpm, 75 rpm and 100 rpm. Screw conveyor mass flow and torque data are taken for analysis. The DEM simulation results at a speed of 100 rpm with inclination of 00 is 21,2 ton/hour and the required power of 1.58 HP. Different results are obtained in modelling with an inclination of 450, the capacity drops to 8,6 ton/hour with the required power of 11.8 HP. It can be seen that the capacity reduction due to inclination reaches more than 50% with a significant increase in power.